Cerebral cholesterol granuloma: case report Granuloma de colesterol cerebral: relato de caso - Rodrigo Mendonça; Cleiton Schweitzer Peron; Marco Antônio Stefani; Pasquale Gallo (Arquivos de Neuro-Psiquiatria, 2007)
Intracranial cholesterol granulomas are rare lesions, and have been registered in petrous apex region. The presence of an intracerebral cholesterol granuloma is an uncommun event. We report the case of a 20-years-old woman who undergone craniotomy for resection of a temporal mass. Pathologic examination show a cholesterol granuloma. Granulomas de colesterol intracranianos são lesões raras, sendo observados na região do ápice petroso. A ocorrência de granuloma de colesterol intracerebral é um evento incomum. Relata-se o caso de mulher de 20 anos submetida a craniotomia para ressecção de processo expansivo temporal, com exame anátomo-patológico evidenciando um granuloma de colesterol.